Preliminary experience with resistin assessment in common population. - Stejskal, David; Prošková, Jitka; Adamovská, Sylva; Juráková, Renata; Bartek, Josef (Biomedical papers, 2002)
Resistin is a signal peptide produced by adipose tissue. Mice models have confirmed that resistin may play an important role in insulin resistance. Its function in the human organism has not been elucidated yet. Since in common population the resistin concentrations are not known (no validated commercial set is available), we performed resistin assessment using the ELISA method (with satisfying analytical characteristics) in a population of 123 non-obese probands without signs of insulin resistance and/or inflammation. Mean resistin values amounted to 14.3 ng/ml (reference limit of 7.3-21.3 ng/ml).
Keywords: Resistin / Serum concentration